2021
DOI: 10.3390/ijms221810021
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Side of NCAM Family: NCAM2, a Key Cytoskeleton Organization Molecule Regulating Multiple Neural Functions

Abstract: Although it has been over 20 years since Neural Cell Adhesion Molecule 2 (NCAM2) was identified as the second member of the NCAM family with a high expression in the nervous system, the knowledge of NCAM2 is still eclipsed by NCAM1. The first studies with NCAM2 focused on the olfactory bulb, where this protein has a key role in axonal projection and axonal/dendritic compartmentalization. In contrast to NCAM1, NCAM2’s functions and partners in the brain during development and adulthood have remained largely unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 180 publications
0
19
1
Order By: Relevance
“…Interestingly, orosomucoid-1 (ORM1), the host gene of hsa_circ_0001883, is an acute phase response (APR) protein that regulates angiogenesis by stimulating VEGF ( Luo et al, 2015 ). Increasing evidence suggests that retinal neuronal degeneration started in the early stages of DR ( Srinivasan et al, 2017 ; Rolev et al, 2021 ), while hsa_circ_0095008 is spliced from neural cell adhesion molecule 2 (NCAM2) that modulates neuronal morphogenesis and differentiation ( Parcerisas et al, 2021 ), which also indicates that circRNAs play a potential role in the early stages of DR. Moreover, circRNAs mainly exert their regulatory functions as miRNA sponges.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, orosomucoid-1 (ORM1), the host gene of hsa_circ_0001883, is an acute phase response (APR) protein that regulates angiogenesis by stimulating VEGF ( Luo et al, 2015 ). Increasing evidence suggests that retinal neuronal degeneration started in the early stages of DR ( Srinivasan et al, 2017 ; Rolev et al, 2021 ), while hsa_circ_0095008 is spliced from neural cell adhesion molecule 2 (NCAM2) that modulates neuronal morphogenesis and differentiation ( Parcerisas et al, 2021 ), which also indicates that circRNAs play a potential role in the early stages of DR. Moreover, circRNAs mainly exert their regulatory functions as miRNA sponges.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the effects of NCAM2 are not known. The interaction of NCAM2 with microtubule-associated proteins, such as MAP1B, that also participate in the regulation of neuronal migration has also been described (González-Billault et al, 2005; Kawauchi & Hoshino, 2008; Parcerisas et al, 2020; Parcerisas, Ortega-gascó, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that the overexpression of NCAM1 reduces baseline levels of EGFR, enhancing the EGF-induced receptor down-regulation, and that the depletion of NCAM2 increases the levels of the ErbB2 growth factor receptor (Povlsen et al 2008; Deleyrolle et al 2015). Another possibility is that NCAM2 expression could cause cytoskeletal rearrangements, which are known to influence the neurogenetic process (Compagnucci et al, 2016; Parcerisas et al, 2020; Parcerisas, Ortega-gascó, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations